Darwinian Evolution of Intelligence - Phillips, J. C. (Frontiers in Bioinformatics, 2022)
Intelligence is often discussed in terms of neural networks in the cerebral cortex, whose evolution has presumably been influenced by Darwinian selection. Here we present molecular evidence that one of the many kinesin motors, Kif14, has evolved to exhibit special features in its amino acid sequence that could have evolved to improve neural networks. The improvement is quantified by comparison of Kif14 sequences for 13 species. The special feature is synchronization-enhancing level sets of hydrophobic extrema in water wave profiles based on several hydropathic scales. The most effective scale is a new one based on fractals, indicative of approach of globular curvatures to self-organized criticality. It is possible that Kif14 is a key to humans’ mental abilities.